Direct Cash Transfer Effect on Children Quality in Women’s Household in Indonesia - Ni Putu Wiwin Setyari; Putu Ayu Pramitha Purwanti (Signifikan: Jurnal Ilmu Ekonomi, 2022)
Many studies confirm the importance of the role of women in the effectiveness of government programs, especially the programs aimed at improving family welfare. This study aims to examine the effect of the government program of direct cash transfers (BLT) on the human capital of children in households headed by women in Indonesia. Data for the study was obtained from IFLS (wave 5) and analyzed with multiple linear regression. The analysis results show that there is a negative effect of BLT on the education of children. Previous studies state this is due to the changing behavior of the recipient households or the spillover effects on the non-recipient households. This research proposes a different reason, such as social discrimination against households headed by women. The solid patriarchal culture in Indonesia often ignores female-headed households, so the number of households receiving social protection programs is relatively very limited.How to Cite:Setyari, N. P. W., & Purwanti, P. A. P (2022). Direct Cash Transfer on Children Quality in Women’s Household in Indonesia. Signifikan: Jurnal Ilmu Ekonomi, 11(1), 83-94. https://doi.org/10.15408/sjie.v11i1.22769.